Composite film based on nano waterproof coating and preparation method thereof

Through the composite film preparation method based on nano-waterproof coatings, the problems of insufficient waterproofing, wear resistance and corrosion resistance of the existing composite film are solved, and the significant performance improvement of the composite film is achieved, extending the service life and reducing maintenance costs.

CN119431859AInactive Publication Date: 2025-02-14深圳市兴威格科技有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411801631.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing composite films have shortcomings in waterproofing, wear resistance and corrosion resistance, resulting in short service life and high maintenance costs, which affects the reliability and safety of the product.

Method used

Using a composite film preparation method based on nano-waterproof coatings, the polyurethane-acrylic waterproof structure and thiolated sepiolite filler are formed by reacting and mixing materials such as acrylic prepolymer, silicone modified isocyanate and nano-sepiolite. Combined with ultraviolet light and heating treatment, a composite film with excellent waterproof, wear resistance and corrosion resistance is obtained.

Benefits of technology

It significantly improves the waterproofness, wear resistance and corrosion resistance of the composite film, extends the service life of the material, reduces maintenance costs, and improves the reliability and safety of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of composite films, in particular to a composite film based on nano waterproof paint and a preparation method of the composite film. The preparation method comprises the following steps: adding acrylic acid, butyl acrylate, vinyl organic silicon, dodecafluoroheptyl methacrylate, azodiisobutyronitrile, mercaptoethanol and acetone to prepare an acrylic acid prepolymer; the siloxane modified isocyanate, the acrylic acid modified isocyanate and hydroxyethyl acrylate are sequentially added into the acrylic acid prepolymer, and the polyurethane modified acrylic emulsion is prepared. And treating the surface of the nano sepiolite material by using a silane coupling agent to prepare the sulfhydrylated sepiolite. And mixing the polyurethane modified acrylic emulsion, sulfhydrylated sepiolite and a 1173 initiator, so as to obtain the nano waterproof coating. And coating the surface of the polyester film with the nano waterproof coating to obtain a finished product. The finished product prepared by the invention has good waterproofness, wear resistance and corrosion resistance, so that the finished product has a wide application prospect in the technical field of composite films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite membranes, in particular to a composite membrane based on a nano waterproof coating and a preparation method thereof. Background Art

[0002] With the continuous advancement of science and technology, innovations in the field of materials science are bringing revolutionary changes to various industries. The following are several important applications and values ​​of composite films based on nano waterproof coatings in modern society. 1. High efficiency and versatility: The composite film prepared by nano waterproof coatings not only has excellent waterproof performance, but also has many other functions at the same time, such as anti-corrosion and wear resistance. This multifunctional property makes it have broad application prospects in the automotive industry, aerospace, electronic equipment and other fields. For example, in automobile manufacturing, this composite film can be applied to the surface of the vehicle body to improve the durability and aesthetics of the vehicle while reducing maintenance costs. In the field of electronic equipment, this material can be applied to screens and shells to provide effective waterproof protection and extend the service life of the equipment. 2. Environmental protection and sustainability: Against the backdrop of global climate change and resource shortages, environmental protection and sustainability have become important issues in modern society. The composite film prepared by nano waterproof coatings has excellent waterproof performance and can effectively reduce the waste of water resources. For example, in the field of construction, this composite film can be applied to roofs, walls and windows, significantly reducing water penetration and reducing the maintenance cost and energy consumption of buildings. In addition, nano waterproof coatings themselves are generally environmentally friendly, using non-toxic, low-volatile materials, which meets the requirements of modern sustainable development.

[0003] In the construction industry, building materials are easily damaged by moisture, leading to structural damage and material aging; in the automotive industry, the surface of the vehicle body is easily worn by sand, dust and other impurities, which reduces the overall life of the vehicle. In the aerospace field, the surface of aircraft and rockets is threatened by corrosion and wear, which seriously affects flight safety and mission success. Therefore, it is urgent to improve the waterproof performance, wear resistance and corrosion resistance of composite membranes to extend the service life of materials, reduce maintenance costs, and improve product reliability and safety. This will not only promote technological innovation and industrial upgrading, but also bring greater economic and social benefits to society. With the continuous development of materials science and engineering technology, high-performance composite membranes will play an important role in more fields.

[0004] In order to overcome the defects of the prior art, the present invention provides a composite membrane based on a nano waterproof coating and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide a composite film based on a nano waterproof coating and a preparation method thereof, so as to solve the problems in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a composite film based on a nano waterproof coating comprises the following steps: Step 1: Mix acrylic acid, butyl acrylate, vinyl silicone, dodecafluoroheptyl methacrylate, azobisisobutyronitrile, mercaptoethanol and acetone, then drop hydroxyethyl acrylate and react in a water bath at 65-70°C for 25-30h to obtain an acrylic prepolymer; mix acrylic prepolymer, siloxane-modified isocyanate, dibutyltin dilaurate and acetone, react at 50-60°C for 3-4h, then add acrylic modified isocyanate and continue to react for 2-3h, then add hydroxyethyl acrylate and continue to react for 4-5h to obtain a polyurethane modified acrylic prepolymer; mix triethylamine and polyurethane modified acrylic prepolymer, add water for hydration, and remove acetone by reduced pressure distillation to obtain a polyurethane modified acrylic emulsion; Step 2: adding the nano-sepiolite material to a 2-3 mol / L hydrochloric acid solution, stirring and reacting at 80-90° C. for 10-12 hours, filtering, washing and drying after the reaction to obtain an acidified sepiolite material; then adding the acidified sepiolite material to a 3-mercaptopropyltrimethoxysilane solution, stirring and reacting at 95-100° C. for 4-5 hours, washing and vacuum drying after the reaction to obtain a thiolated sepiolite; Step 3: Mix the polyurethane modified acrylic emulsion, the thiol sepiolite and the 1173 initiator, and stir them thoroughly to obtain a nano waterproof coating; apply the nano waterproof coating to the surface of the polyester film, irradiate with ultraviolet light for 10-15 minutes, and heat at 110-120° C. for 30-40 minutes to obtain a finished product.

[0007] More optimally, in step one, the content of each solute component of the acrylic prepolymer is: by mass fraction, 5.5-6.5% acrylic acid, 20-25% butyl acrylate, 20-25% vinyl silicone, 15-20% dodecafluoroheptyl methacrylate, 2.5-3.0% azobisisobutyronitrile, 1-2% mercaptoethanol, and the balance is hydroxyethyl acrylate.

[0008] More optimally, in step 1, the reaction molar ratio of hydroxyl groups in acrylic prepolymer, isocyanate groups in siloxane-modified isocyanate, isocyanate groups in acrylic modified isocyanate, and hydroxyl groups in hydroxyethyl acrylate is 4: (5.0-6.0): (2.0-2.5): (2.5-3.0).

[0009] More optimally, isophorone diisocyanate, dibutyltin dilaurate, and acetone are mixed, and a mixture of hydroxyethyl acrylate, 4-methoxyphenol and acetone is added dropwise, and the mixture is fully reacted at 40-45°C for 6-10 hours to obtain acrylic acid-modified isocyanate; isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, dibutyltin dilaurate, and acetone are mixed, the temperature is raised to 60-70°C, and the mixture is reacted at a constant temperature for 4-6 hours to obtain siloxane-modified isocyanate.

[0010] More optimally, when preparing acrylic modified isocyanate, the reaction molar ratio of isophorone diisocyanate and hydroxyethyl acrylate is (1.2-1.4):1; when preparing siloxane modified isocyanate, the reaction molar ratio of the isocyanate group in isophorone diisocyanate and the hydroxyl group in hydroxypropyl polydimethylsiloxane is (2.0-2.3):1.

[0011] More optimally, in step one, 3-trimethoxysilane propyl acrylate, dimethylvinyl chlorosilane and isopropanol are mixed, stirred for 5-8 minutes, deionized water is then added dropwise for 1.0-1.5 hours, stirring is continued for 4-5 hours, and then deionized water is added and stirred overnight. After the reaction is completed, the mixture is extracted, washed, dried, desolventized and purified to obtain vinyl silicone.

[0012] More optimally, the reaction mass ratio of 3-trimethoxysilane propyl acrylate and dimethylvinyl chlorosilane is (1.0-1.2):3.

[0013] More optimally, in step 2, the reaction mass ratio of the acidified sepiolite material and 3-mercaptopropyltrimethoxysilane is 2:(5-6).

[0014] More optimally, in step three, the prepared polyurethane-modified acrylic emulsion and thiolated sepiolite are mixed and reacted in a molar ratio of double bond:thiol=1:(0.3-0.7), the amount of 1173 initiator is 1-2wt% of the total amount of reactants; and the ultraviolet light wavelength is 365nm.

[0015] Beneficial effects of the present invention: The present invention is characterized in that, in step 1, acrylic acid, butyl acrylate, vinyl silicone, dodecafluoroheptyl methacrylate, azobisisobutyronitrile, mercaptoethanol and acetone are added to prepare an acrylic acid prepolymer. This step introduces functional groups hydroxyl, carboxyl, fluorine and siloxane groups through free radical copolymerization, and the wear resistance and corrosion resistance of the material can be effectively improved by introducing the above groups.

[0016] Furthermore, the acrylic prepolymer containing hydroxyl groups is first reacted with siloxane-modified isocyanate, which can generate a polyurethane-acrylic waterproof structure on the one hand, and can introduce siloxane groups to enhance the wear and corrosion resistance of the material for the second time. Adding acrylic modified isocyanate to continue to react with the acrylic prepolymer containing hydroxyl groups can generate a polyurethane-acrylic waterproof structure on the one hand, and introduce double bonds to obtain a photocurable structure on the other hand, which is used for the effective photocuring reaction of subsequent coatings. In the above reaction, there are still some unreacted isocyanate groups after the reaction of acrylic prepolymer and siloxane-modified isocyanate, so hydroxyethyl acrylate is introduced to react with the remaining isocyanate groups, and the photocurable double bond structure and polyurethane-acrylic waterproof structure can be increased at the same time. In this step, the existing reaction sites are fully utilized through continuous chemical reactions, and new functional groups are successfully introduced. In this process, not only the cross-linked structure between the molecular chains is improved and strengthened, but also the comprehensive performance of the composite material can be significantly improved.

[0017] The feature of the present invention is that, in step 2, the filler nano sepiolite with excellent corrosion resistance and wear resistance is first subjected to acid treatment to obtain an acidified sepiolite material. Then the acidified sepiolite material and 3-mercaptopropyltrimethoxysilane solution are mixed and reacted to obtain thiolated sepiolite. In step 3, polyurethane-modified acrylic emulsion, thiolated sepiolite, and 1173 initiator are mixed and fully stirred to obtain a nano waterproof coating; the nano waterproof coating is applied to the surface of the polyester film, and the finished composite film is obtained by ultraviolet light and heating. In step 3, the polyurethane-modified acrylic emulsion and the thiolated sepiolite filler can quickly undergo a thiol-ene photocuring reaction under the conditions of 1173 initiator and ultraviolet light to obtain a composite film. The composite film prepared by the present invention has good waterproofness, wear resistance, and corrosion resistance, and therefore has broad application prospects in the field of composite film technology. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Source of raw materials: Acrylic paint, provided by Henan Aohui Industrial Coatings Co., Ltd., model ahbxs1101; hydroxypropyl polydimethylsiloxane, provided by Jiande New Materials Co., Ltd., with a hydroxyl content of 1.1wt%; nano-sepiolite material, provided by Xiangtan Yuanyuan Sepiolite Co., Ltd., with a particle size of 200 mesh; polyester film, provided by Shenzhen Hecheng New Materials Technology Co., Ltd., specifically PET film, model TU94.

[0020] Example 1: Step 1: 3-trimethoxysilane propyl acrylate, dimethylvinyl chlorosilane and isopropanol were mixed, stirred for 8 minutes, deionized water was added dropwise for 1.5 hours, and the stirring was continued for 5 hours, and then deionized water was added and stirred overnight. After the reaction was completed, the mixture was extracted, washed, dried, desolventized and purified to obtain vinyl silicone; wherein the reaction mass ratio of 3-trimethoxysilane propyl acrylate to dimethylvinyl chlorosilane was 1.1:3; Acrylic acid, butyl acrylate, vinyl silicone, dodecafluoroheptyl methacrylate, azobisisobutyronitrile, mercaptoethanol and acetone were mixed, and hydroxyethyl acrylate was added dropwise and reacted in a water bath at 70°C for 30 hours to obtain an acrylic acid prepolymer; the contents of each solute component of the acrylic acid prepolymer were: by mass fraction, 6.5% acrylic acid, 25% butyl acrylate, 25% vinyl silicone, 20% dodecafluoroheptyl methacrylate, 3.0% azobisisobutyronitrile, 1% mercaptoethanol, and 19.5% hydroxyethyl acrylate; Isophorone diisocyanate, dibutyltin dilaurate and acetone were mixed, and a mixture of hydroxyethyl acrylate, 4-methoxyphenol and acetone was added dropwise, and the mixture was fully reacted at 45°C for 10 hours to obtain acrylic acid-modified isocyanate; isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, dibutyltin dilaurate and acetone were mixed, and the temperature was raised to 70°C for constant temperature reaction for 6 hours to obtain siloxane-modified isocyanate; when preparing acrylic acid-modified isocyanate, the reaction molar ratio of isophorone diisocyanate and hydroxyethyl acrylate was 1.3:1; when preparing siloxane-modified isocyanate, the reaction molar ratio of isophorone diisocyanate and hydroxypropyl polydimethylsiloxane was 2.1:1; The acrylic prepolymer, siloxane-modified isocyanate, dibutyltin dilaurate and acetone are mixed, reacted at 60°C for 4 hours, and then the acrylic modified isocyanate is added to continue the reaction for 3 hours, and then hydroxyethyl acrylate is added to continue the reaction for 5 hours to obtain a polyurethane-modified acrylic prepolymer; triethylamine and polyurethane-modified acrylic prepolymer are mixed, and water is added to hydrate, and acetone is removed by reduced pressure distillation to obtain a polyurethane-modified acrylic emulsion; the reaction molar ratio of hydroxyl group in acrylic prepolymer, isocyanate group in siloxane-modified isocyanate, isocyanate group in acrylic modified isocyanate and hydroxyl group in hydroxyethyl acrylate is 4:5.5:2.3:2.7; Step 2: adding the nano-sepiolite material to a 3 mol / L hydrochloric acid solution, stirring and reacting at 90°C for 12 hours, filtering, washing and drying after the reaction to obtain an acidified sepiolite material; then adding the acidified sepiolite material to a 3-mercaptopropyltrimethoxysilane solution, stirring and reacting at 100°C for 5 hours, washing and vacuum drying after the reaction to obtain a mercaptolated sepiolite; the reaction mass ratio of the acidified sepiolite material to 3-mercaptopropyltrimethoxysilane is 2:5.5; Step 3: Mix the polyurethane modified acrylic emulsion, thiolated sepiolite and 1173 initiator, and stir them thoroughly to obtain a nano waterproof coating; apply the nano waterproof coating to the surface of the polyester film, irradiate with ultraviolet light for 15 minutes, and heat at 120°C for 40 minutes to obtain a finished product; wherein the prepared polyurethane modified acrylic emulsion and thiolated sepiolite are mixed and reacted in a molar ratio of double bond:thiol=1:0.4, and the amount of 1173 initiator is 1.5wt% of the total amount of reactants; the ultraviolet light wavelength is 365nm.

[0021] Example 2: Step 1: 3-trimethoxysilane propyl acrylate, dimethylvinyl chlorosilane and isopropanol were mixed, stirred for 7 minutes, deionized water was added dropwise for 1.3 hours, and the stirring was continued for 4.5 hours. Then, deionized water was added and stirred overnight. After the reaction was completed, the mixture was extracted, washed, dried, desolventized and purified to obtain vinyl silicone; wherein the reaction mass ratio of 3-trimethoxysilane propyl acrylate to dimethylvinyl chlorosilane was 1.1:3; Acrylic acid, butyl acrylate, vinyl silicone, dodecafluoroheptyl methacrylate, azobisisobutyronitrile, mercaptoethanol and acetone are mixed, and then hydroxyethyl acrylate is added dropwise and reacted in a water bath at 67°C for 27 hours to obtain an acrylic acid prepolymer; the contents of each solute component of the acrylic acid prepolymer are: by mass fraction, 6.5% acrylic acid, 25% butyl acrylate, 25% vinyl silicone, 20% dodecafluoroheptyl methacrylate, 3.0% azobisisobutyronitrile, 1% mercaptoethanol, and 19.5% hydroxyethyl acrylate; Isophorone diisocyanate, dibutyltin dilaurate and acetone were mixed, and a mixture of hydroxyethyl acrylate, 4-methoxyphenol and acetone was added dropwise, and the mixture was fully reacted at 43°C for 7 hours to obtain acrylic acid-modified isocyanate; isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, dibutyltin dilaurate and acetone were mixed, and the temperature was raised to 65°C for constant temperature reaction for 5 hours to obtain siloxane-modified isocyanate; when preparing acrylic acid-modified isocyanate, the reaction molar ratio of isophorone diisocyanate and hydroxyethyl acrylate was 1.3:1; when preparing siloxane-modified isocyanate, the reaction molar ratio of isophorone diisocyanate and hydroxypropyl polydimethylsiloxane was 2.1:1; The acrylic prepolymer, siloxane-modified isocyanate, dibutyltin dilaurate and acetone are mixed, reacted at 55°C for 3.5 hours, then the acrylic modified isocyanate is added and the reaction is continued for 2.5 hours, then hydroxyethyl acrylate is added and the reaction is continued for 4.5 hours to obtain a polyurethane-modified acrylic prepolymer; triethylamine and polyurethane-modified acrylic prepolymer are mixed, and water is added to hydrate, and acetone is removed by reduced pressure distillation to obtain a polyurethane-modified acrylic emulsion; the reaction molar ratio of hydroxyl group in acrylic prepolymer, isocyanate group in siloxane-modified isocyanate, isocyanate group in acrylic modified isocyanate and hydroxyl group in hydroxyethyl acrylate is 4:5.5:2.3:2.7; Step 2: Add the nano-sepiolite material to a 3 mol / L hydrochloric acid solution, stir and react at 85°C for 11 hours, and after the reaction is completed, filter, wash and dry to obtain an acidified sepiolite material; then add the acidified sepiolite material to a 3-mercaptopropyltrimethoxysilane solution, stir and react at 97°C for 4.5 hours, and after the reaction is completed, wash and vacuum dry to obtain a mercaptolated sepiolite; the reaction mass ratio of the acidified sepiolite material to 3-mercaptopropyltrimethoxysilane is 2:5.5; Step 3: Mix the polyurethane modified acrylic emulsion, thiolated sepiolite and 1173 initiator, and stir them thoroughly to obtain a nano waterproof coating; apply the nano waterproof coating to the surface of the polyester film, irradiate with ultraviolet light for 13 minutes, and heat at 115°C for 35 minutes to obtain a finished product; wherein the prepared polyurethane modified acrylic emulsion and thiolated sepiolite are mixed and reacted in a molar ratio of double bond:thiol=1:0.4, and the amount of 1173 initiator is 1.5wt% of the total amount of reactants; the ultraviolet light wavelength is 365nm.

[0022] Example 3: Step 1: 3-trimethoxysilane propyl acrylate, dimethylvinyl chlorosilane and isopropanol were mixed, stirred for 5 minutes, deionized water was added dropwise for 1 hour, the stirring was continued for 4 hours, and then deionized water was added and stirred overnight. After the reaction was completed, the mixture was extracted, washed, dried, desolventized and purified to obtain vinyl silicone; wherein the reaction mass ratio of 3-trimethoxysilane propyl acrylate to dimethylvinyl chlorosilane was 1.1:3; Acrylic acid, butyl acrylate, vinyl silicone, dodecafluoroheptyl methacrylate, azobisisobutyronitrile, mercaptoethanol and acetone are mixed, and then hydroxyethyl acrylate is added dropwise and reacted in a water bath at 65°C for 25 hours to obtain an acrylic acid prepolymer; the contents of each solute component of the acrylic acid prepolymer are: by mass fraction, 6.5% acrylic acid, 25% butyl acrylate, 25% vinyl silicone, 20% dodecafluoroheptyl methacrylate, 3.0% azobisisobutyronitrile, 1% mercaptoethanol, and 19.5% hydroxyethyl acrylate; Isophorone diisocyanate, dibutyltin dilaurate and acetone were mixed, and a mixture of hydroxyethyl acrylate, 4-methoxyphenol and acetone was added dropwise, and the mixture was fully reacted at 40°C for 6 hours to obtain acrylic acid-modified isocyanate; isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, dibutyltin dilaurate and acetone were mixed, and the temperature was raised to 60°C for constant temperature reaction for 4 hours to obtain siloxane-modified isocyanate; when preparing acrylic acid-modified isocyanate, the reaction molar ratio of isophorone diisocyanate and hydroxyethyl acrylate was 1.3:1; when preparing siloxane-modified isocyanate, the reaction molar ratio of isophorone diisocyanate and hydroxypropyl polydimethylsiloxane was 2.1:1; The acrylic prepolymer, siloxane-modified isocyanate, dibutyltin dilaurate and acetone are mixed, reacted at 50°C for 3 hours, and then the acrylic modified isocyanate is added to continue the reaction for 2 hours, and then hydroxyethyl acrylate is added to continue the reaction for 4 hours to obtain a polyurethane-modified acrylic prepolymer; triethylamine and polyurethane-modified acrylic prepolymer are mixed, and water is added to hydrate, and acetone is removed by reduced pressure distillation to obtain a polyurethane-modified acrylic emulsion; the reaction molar ratio of hydroxyl group in acrylic prepolymer, isocyanate group in siloxane-modified isocyanate, isocyanate group in acrylic modified isocyanate and hydroxyl group in hydroxyethyl acrylate is 4:5.5:2.3:2.7; Step 2: adding the nano-sepiolite material to a 3 mol / L hydrochloric acid solution, stirring and reacting at 80°C for 10 hours, filtering, washing and drying after the reaction to obtain an acidified sepiolite material; then adding the acidified sepiolite material to a 3-mercaptopropyltrimethoxysilane solution, stirring and reacting at 95°C for 4 hours, washing and vacuum drying after the reaction to obtain a mercaptolated sepiolite; the reaction mass ratio of the acidified sepiolite material to 3-mercaptopropyltrimethoxysilane is 2:5.5; Step 3: Mix the polyurethane modified acrylic emulsion, thiolated sepiolite and 1173 initiator, and stir them thoroughly to obtain a nano waterproof coating; apply the nano waterproof coating to the surface of the polyester film, irradiate with ultraviolet light for 10 minutes, and heat at 110°C for 30 minutes to obtain a finished product; wherein the prepared polyurethane modified acrylic emulsion and thiolated sepiolite are mixed and reacted in a molar ratio of double bond:thiol=1:0.4, and the amount of 1173 initiator is 1.5wt% of the total amount of reactants; the ultraviolet light wavelength is 365nm.

[0023] Comparative Example 1: Vinyl silicone and siloxane-modified isocyanate were removed, and the rest was the same as Example 1, and the specific steps were as follows: Step 1: acrylic acid, butyl acrylate, dodecafluoroheptyl methacrylate, azobisisobutyronitrile, mercaptoethanol and acetone were mixed, and hydroxyethyl acrylate was added dropwise and reacted in a water bath at 70° C. for 30 hours to obtain an acrylic acid prepolymer; the content of each solute component of the acrylic acid prepolymer was: by mass fraction, 6.5% acrylic acid, 50% butyl acrylate, 20% dodecafluoroheptyl methacrylate, 3.0% azobisisobutyronitrile, 1% mercaptoethanol, and 19.5% hydroxyethyl acrylate; Mix isophorone diisocyanate, dibutyltin dilaurate and acetone, then drop a mixture of hydroxyethyl acrylate, 4-methoxyphenol and acetone, and fully react at 45°C for 10 hours to obtain acrylic acid modified isocyanate; when preparing acrylic acid modified isocyanate, the reaction molar ratio of isophorone diisocyanate and hydroxyethyl acrylate is 1.3:1; Acrylic prepolymer, acrylic modified isocyanate, dibutyltin dilaurate and acetone are mixed and reacted at 60°C for 3 hours to obtain polyurethane modified acrylic prepolymer; triethylamine and polyurethane modified acrylic prepolymer are mixed, and water is added to hydrate, and acetone is removed by reduced pressure distillation to obtain polyurethane modified acrylic emulsion; the reaction molar ratio of hydroxyl group in acrylic prepolymer and isocyanate group in acrylic modified isocyanate is 4:2.3; Step 2: adding the nano-sepiolite material to a 3 mol / L hydrochloric acid solution, stirring and reacting at 90°C for 12 hours, filtering, washing and drying after the reaction to obtain an acidified sepiolite material; then adding the acidified sepiolite material to a 3-mercaptopropyltrimethoxysilane solution, stirring and reacting at 100°C for 5 hours, washing and vacuum drying after the reaction to obtain a mercaptolated sepiolite; the reaction mass ratio of the acidified sepiolite material to 3-mercaptopropyltrimethoxysilane is 2:5.5; Step 3: Mix the polyurethane modified acrylic emulsion, thiolated sepiolite and 1173 initiator, and stir them thoroughly to obtain a nano waterproof coating; apply the nano waterproof coating to the surface of the polyester film, irradiate with ultraviolet light for 15 minutes, and heat at 120°C for 40 minutes to obtain a finished product; wherein the prepared polyurethane modified acrylic emulsion and thiolated sepiolite are mixed and reacted in a molar ratio of double bond:thiol=1:0.4, and the amount of 1173 initiator is 1.5wt% of the total amount of reactants; the ultraviolet light wavelength is 365nm.

[0024] Comparative Example 2: Step 2 is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: 3-trimethoxysilane propyl acrylate, dimethylvinyl chlorosilane and isopropanol are mixed, stirred for 8 minutes, and then deionized water is added dropwise for 1.5 hours, and the stirring is continued for 5 hours, and then deionized water is added and stirred overnight. After the reaction is completed, the mixture is extracted, washed, dried, desolventized and purified to obtain vinyl silicone; wherein the reaction mass ratio of 3-trimethoxysilane propyl acrylate to dimethylvinyl chlorosilane is 1.1:3; Acrylic acid, butyl acrylate, vinyl silicone, dodecafluoroheptyl methacrylate, azobisisobutyronitrile, mercaptoethanol and acetone were mixed, and hydroxyethyl acrylate was added dropwise and reacted in a water bath at 70°C for 30 hours to obtain an acrylic acid prepolymer; the contents of each solute component of the acrylic acid prepolymer were: by mass fraction, 6.5% acrylic acid, 25% butyl acrylate, 25% vinyl silicone, 20% dodecafluoroheptyl methacrylate, 3.0% azobisisobutyronitrile, 1% mercaptoethanol, and 19.5% hydroxyethyl acrylate; Isophorone diisocyanate, dibutyltin dilaurate and acetone were mixed, and a mixture of hydroxyethyl acrylate, 4-methoxyphenol and acetone was added dropwise, and the mixture was fully reacted at 45°C for 10 hours to obtain acrylic acid-modified isocyanate; isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, dibutyltin dilaurate and acetone were mixed, and the temperature was raised to 70°C for constant temperature reaction for 6 hours to obtain siloxane-modified isocyanate; when preparing acrylic acid-modified isocyanate, the reaction molar ratio of isophorone diisocyanate and hydroxyethyl acrylate was 1.3:1; when preparing siloxane-modified isocyanate, the reaction molar ratio of isophorone diisocyanate and hydroxypropyl polydimethylsiloxane was 2.1:1; The acrylic prepolymer, siloxane-modified isocyanate, dibutyltin dilaurate and acetone are mixed, reacted at 60°C for 4 hours, and then the acrylic modified isocyanate is added to continue the reaction for 3 hours, and then hydroxyethyl acrylate is added to continue the reaction for 5 hours to obtain a polyurethane-modified acrylic prepolymer; triethylamine and polyurethane-modified acrylic prepolymer are mixed, and water is added to hydrate, and acetone is removed by reduced pressure distillation to obtain a polyurethane-modified acrylic emulsion; the reaction molar ratio of hydroxyl group in acrylic prepolymer, isocyanate group in siloxane-modified isocyanate, isocyanate group in acrylic modified isocyanate and hydroxyl group in hydroxyethyl acrylate is 4:5.5:2.3:2.7; Step 2: Mix the polyurethane modified acrylic emulsion and the 1173 initiator, and stir them thoroughly to obtain a coating; apply the coating to the surface of the polyester film, irradiate with ultraviolet light for 15 minutes, and heat at 120°C for 40 minutes to obtain a finished product; wherein the amount of the 1173 initiator is 1.5wt% of the total amount of the reactants; and the ultraviolet light wavelength is 365nm.

[0025] Comparative Example 3: The nano waterproof coating prepared by the present invention is replaced by the acrylic coating provided by Henan Aohui Industrial Coatings Co., Ltd., and the rest is the same as Example 1. The specific steps are as follows: apply the acrylic coating to the surface of the polyester film, heat it at 120°C for 3h, and obtain the finished product.

[0026] Detection test: Waterproof test: The composite membranes prepared in Examples 1-3 and Comparative Examples 1-3 were used as samples, and half of the sample area was immersed in distilled water for 200 hours, and then the surface conditions of the immersed and non-immersed parts were observed.

[0027] Corrosion resistance test: The composite films prepared in Examples 1-3 and Comparative Examples 1-3 were cut into samples of 150 mm × 100 mm × 1 mm. According to GB / T 1771-2007, a sodium chloride solution with a mass concentration of 55 g / L was prepared. The pH of the spray solution in the salt spray test box was set to 6.5 and the temperature was set to 35°C. The corrosion resistance was judged based on the corrosion resistance salt spray time.

[0028] Abrasion resistance test: The nano waterproof coating prepared in Examples 1-3 and Comparative Examples 1-3 was coated on the surface of a glass sheet, and then subjected to ultraviolet light and heating (selected according to the parameters of the Examples and Comparative Examples) to obtain a coating film. According to GB / T1768-79 standard, the coating was polished with 400# sandpaper, and the weight loss rate was calculated by testing the mass of the coating film before and after polishing. The results are shown in the following table: Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. From the experimental data, it can be seen that the various properties of the samples have no obvious fluctuations.

[0029] Comparative Example 1: The vinyl silicone and siloxane-modified isocyanate were removed, and the rest was the same as Example 1. It can be seen from the experimental data that, compared with Example 1, the weight loss rate became 16.87%, the corrosion salt spray time became 717h, and the waterproof effect did not change significantly. The reasons were analyzed as follows: vinyl silicone and siloxane-modified isocyanate contain more siloxane groups. The presence of siloxane groups can form a thin lubricating layer, reduce the friction coefficient, thereby reducing direct contact and wear between materials, and effectively improve the wear resistance of the materials; therefore, after removing the vinyl silicone and siloxane-modified isocyanate, the weight loss rate of the coating increased and the wear resistance decreased.

[0030] Comparative Example 2: Step 2 is removed, and the rest is the same as Example 1. It can be seen from the experimental data that, compared with Example 1, the weight loss rate becomes 18.43%, the corrosion resistance salt spray time is 707h, and the waterproof effect has no obvious change. The reason is analyzed as follows: the thiolated sepiolite prepared in step 2 has the characteristics of high chemical stability and excellent wear resistance. Therefore, after the preparation of the thiolated sepiolite is removed, the weight loss rate of the coating increases and the wear resistance decreases.

[0031] Comparative Example 3: The nano waterproof coating prepared by the present invention is replaced by an acrylic coating provided by Henan Aohui Industrial Coatings Co., Ltd., and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the weight loss rate becomes 27.59%, the corrosion resistance salt spray time becomes 573h, and the surface of the sample is obviously peeled off and foamed. The reasons are analyzed as follows: the nano waterproof coating prepared by the present invention has a polyurethane-acrylic cross-linked waterproof structure, a fluorine group corrosion-resistant structure, a siloxane group wear-resistant structure and a sepiolite material, so it has good waterproofness, wear resistance and corrosion resistance. Therefore, after replacing the nano waterproof coating prepared by the present invention, the weight loss rate of the coating increases, the waterproof effect of the coating surface deteriorates, and the corrosion resistance salt spray time becomes shorter.

[0032] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0033] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite film based on a nano waterproof coating, characterized in that: The following steps are involved: Step 1: Mix acrylic acid, butyl acrylate, vinyl silicone, dodecafluoroheptyl methacrylate, azobisisobutyronitrile, mercaptoethanol and acetone, then drop hydroxyethyl acrylate and react in a water bath at 65-70°C for 25-30h to obtain an acrylic prepolymer; mix acrylic prepolymer, siloxane-modified isocyanate, dibutyltin dilaurate and acetone, react at 50-60°C for 3-4h, then add acrylic modified isocyanate and continue to react for 2-3h, then add hydroxyethyl acrylate and continue to react for 4-5h to obtain a polyurethane modified acrylic prepolymer; mix triethylamine and polyurethane modified acrylic prepolymer, add water for hydration, and remove acetone by reduced pressure distillation to obtain a polyurethane modified acrylic emulsion; Step 2: adding the nano-sepiolite material to a 2-3 mol / L hydrochloric acid solution, stirring and reacting at 80-90° C. for 10-12 hours, filtering, washing and drying after the reaction to obtain an acidified sepiolite material; then adding the acidified sepiolite material to a 3-mercaptopropyltrimethoxysilane solution, stirring and reacting at 95-100° C. for 4-5 hours, washing and vacuum drying after the reaction to obtain a thiolated sepiolite; Step 3: Mix the polyurethane modified acrylic emulsion, the thiol sepiolite and the 1173 initiator, and stir them thoroughly to obtain a nano waterproof coating; apply the nano waterproof coating to the surface of the polyester film, irradiate with ultraviolet light for 10-15 minutes, and heat at 110-120° C. for 30-40 minutes to obtain a finished product.

2. The method for preparing a composite film based on a nano waterproof coating according to claim 1, characterized in that: In step 1, the content of each solute component of the acrylic prepolymer is: by mass fraction, 5.5-6.5% acrylic acid, 20-25% butyl acrylate, 20-25% vinyl silicone, 15-20% dodecafluoroheptyl methacrylate, 2.5-3.0% azobisisobutyronitrile, 1-2% mercaptoethanol, and the balance is hydroxyethyl acrylate.

3. The method for preparing a composite film based on a nano waterproof coating according to claim 1, characterized in that: In step 1, the reaction molar ratio of hydroxyl groups in acrylic prepolymer, isocyanate groups in siloxane-modified isocyanate, isocyanate groups in acrylic modified isocyanate, and hydroxyl groups in hydroxyethyl acrylate is 4: (5.0-6.0): (2.0-2.5): (2.5-3.0).

4. The method for preparing a composite film based on a nano waterproof coating according to claim 3, characterized in that: Mix isophorone diisocyanate, dibutyltin dilaurate and acetone, then add a mixture of hydroxyethyl acrylate, 4-methoxyphenol and acetone, and react at 40-45°C for 6-10 hours to obtain acrylic acid modified isocyanate; mix isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, dibutyltin dilaurate and acetone, heat to 60-70°C and react at a constant temperature for 4-6 hours to obtain siloxane modified isocyanate.

5. The method for preparing a composite film based on a nano waterproof coating according to claim 4, characterized in that: When preparing acrylic modified isocyanate, the reaction molar ratio of isophorone diisocyanate and hydroxyethyl acrylate is (1.2-1.4):1; when preparing siloxane modified isocyanate, the reaction molar ratio of isocyanate group in isophorone diisocyanate and hydroxyl group in hydroxypropyl polydimethylsiloxane is (2.0-2.3):

1.

6. The method for preparing a composite film based on a nano waterproof coating according to claim 1, characterized in that: In step 1, 3-trimethoxysilane propyl acrylate, dimethylvinyl chlorosilane and isopropanol are mixed, stirred for 5-8 minutes, deionized water is added dropwise for 1.0-1.5 hours, stirring is continued for 4-5 hours, and then deionized water is added and stirred overnight. After the reaction is completed, the vinyl silicone is obtained by extraction, washing, drying, solvent removal and purification.

7. The method for preparing a composite film based on a nano waterproof coating according to claim 6, characterized in that: The reaction mass ratio of 3-trimethoxysilane propyl acrylate and dimethylvinyl chlorosilane is (1.0-1.2):

3.

8. The method for preparing a composite film based on a nano waterproof coating according to claim 1, characterized in that: In step 2, the reaction mass ratio of the acidified sepiolite material and 3-mercaptopropyltrimethoxysilane is 2:(5-6).

9. The method for preparing a composite film based on a nano waterproof coating according to claim 1, characterized in that: In step three, the prepared polyurethane modified acrylic emulsion and mercapto-modified sepiolite are mixed and reacted in a molar ratio of double bond: mercapto group = 1: (0.3-0.7), and the amount of 1173 initiator is 1-2wt% of the total amount of reactants; the ultraviolet light wavelength is 365nm.

10. A composite membrane based on nano waterproof coating, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Long-acting, stable, flexible, impact-resistant and resistance-reducing protective film and preparation process thereof

    CN120923842A

  • Nano three-proofing adhesive for waterproof protection of PCB (Printed Circuit Board) and preparation method of nano three-proofing adhesive

    CN121914667A